The Influence of CEO Characteristics on Firm Value: The Mediating Role of Environmental, Social, and Governance (ESG) Performance among Indonesian Listed Companies 2022-2024 - Sanny Aurelia Febri Evelyn Wijaya; Lintang Venusita (Majapahit Journal of Islamic Finance and Management, 2026)
This study investigates the influence of CEO characteristics, namely gender, education, and tenure, on firm value, with Environmental, Social, and Governance (ESG) performance acting as a mediating variable. As sustainability practices become increasingly important in corporate governance, the role of chief executive officers in shaping ESG initiatives and enhancing firm value has attracted growing academic and practical attention. However, empirical evidence regarding the relationship between CEO characteristics, ESG performance, and firm value remains inconsistent, particularly in emerging markets such as Indonesia. This research employs a quantitative approach using secondary data collected from annual reports, sustainability reports, and financial statements of companies listed on the Indonesia Stock Exchange (IDX) during 2022-2024. Firm value is measured using Tobin's Q, while ESG performance is measured using ESG disclosure scores. CEO gender, education, and tenure represent the independent variables. The data are analyzed using multiple linear regression and Sobel tests to examine the mediating effect of ESG. The findings indicate that CEO characteristics have varying effects on ESG performance and firm value. ESG performance significantly contributes to enhancing firm value and partially mediates the relationship between certain CEO characteristics and firm value. These results support the Upper Echelons Theory, suggesting that organizational outcomes are influenced by executives' demographic characteristics, and Stakeholder Theory, emphasizing that sustainability practices create long-term value for firms. This study contributes to the literature on corporate governance and sustainable business by providing empirical evidence from Indonesian listed companies. The findings also offer practical implications for corporate boards and investors in considering CEO characteristics and ESG implementation as strategic factors for improving firm value.